2019
DOI: 10.3390/jcm8081112
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Stress Response during Vaginal Delivery and Elective Cesarean Section through Assessment of Levels of Cortisol, Interleukin 6 (IL-6), Growth Hormone (GH) and Insulin-Like Growth Factor 1 (IGF-1)

Abstract: Background: How do stress related phenomena during labor differ between vaginal delivery (VD) and elective cesarean section (CS), remains of heightened interest. The purpose of this study is to investigate discrepancies regarding the stress response during VD and CS. Methods: Cortisol, interleukin 6 (IL-6), growth hormone (GH) and insulin-like growth factor 1 (IGF-1) levels from parturients’ peripheral blood were evaluated on three time-points, namely during the first stage of labor (TP1), two hours post labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Miller et al found the salivary cortisol concentration to gradually increase from the latent to the active phase in low-risk VAG deliveries, with the maximum concentration being observed within two minutes of the onset of labor [70]. In line with our results, some authors have described how VAG deliveries are associated with higher serum cortisol concentrations and more intense inflammation than elective CS deliveries, although the inflammatory response period is shorter than in the case of CS [71][72][73].…”
Section: Discussionsupporting
confidence: 90%
“…Miller et al found the salivary cortisol concentration to gradually increase from the latent to the active phase in low-risk VAG deliveries, with the maximum concentration being observed within two minutes of the onset of labor [70]. In line with our results, some authors have described how VAG deliveries are associated with higher serum cortisol concentrations and more intense inflammation than elective CS deliveries, although the inflammatory response period is shorter than in the case of CS [71][72][73].…”
Section: Discussionsupporting
confidence: 90%
“…[22, 23] There is the contentious possibility, however, that the putative placental microbiota influences composition too, regardless of delivery mode. [24, 25] Another potential mechanism relates to differences between infants born by CS and VD in the intrapartum concentration of cortisol, noradrenaline and other inflammatory chemicals,[26, 27] which may result in long term neuro-immuno-endocrine, epigenetic and other changes which may influence energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Due to improvement in anesthesia procedures, elective cesarean section is less stressful and could be further associated with less intense inflammation. 22,23 In this study, carried out exclusively in term newborns, despite the higher diurnal melatonin content found in colostrum from mothers after cesarean section, the circadian rhythm remained, and higher nocturnal levels were found in this group. This is consistent with previous studies that found higher levels of melatonin in nighttime colostrum after elective cesarean section with respect to emergency cesarean section.…”
Section: Discussionmentioning
confidence: 54%